Tax Aggressiveness and Big4 Audit Firms - Furtado Hartmann, Carla; Martinez, Antonio Lopo (REUNIR Revista de Administração Contabilidade e Sustentabilidade, 2020)
This study examines the influence of external audits by Big4 or non-Big4 firms on the tax aggressiveness of listed Brazilian companies. Also, the research analyzes the impact on tax aggressiveness in the case of audit firm rotation, particularly when a company moves from Big4 to non-Big4 audit firms and vice versa. The sample was composed of 340 non-financial Brazilian companies, with shares traded in the Brazilian stock exchange B3, in the period between 2010 and 2016, and using two metrics to assess tax aggressiveness. The first is the book-tax difference (BTD) that reflects the difference between book income and taxable income. The second metric is the effective tax rate (ETR), which is calculated by dividing the total tax expenses by the earnings before taxes (EBT). The findings show that companies audited by non-Big4 firms are more aggressive than those audited by Big4 firms. As for moving from Big4 to non-Big4 firms, the results are not sufficiently clear to state whether companies become more or less tax aggressive.